2010
DOI: 10.1103/physreva.81.062129
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of randomness and arrow of time in quantum walks

Abstract: CitationShikano, Yutaka et al. "Emergence of randomness and arrow of time in quantum walks." Physical Review A 81.6 (2010): 062129.Quantum walks are powerful tools not only for constructing the quantum speedup algorithms but also for describing specific models in physical processes. Furthermore, the discrete time quantum walk has been experimentally realized in various setups. We apply the concept of the quantum walk to the problems in quantum foundations. We show that randomness and the arrow of time in the q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…In this section we will consider a succession of unitary evolutions of the QW followed by a process of chirality-andposition measurement [13,14]. Let us take the origin as the initial position of the random walker with the initial condition |Ψ (0)⟩ of Eq.…”
Section: Periodic Measurements In the Chiralitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this section we will consider a succession of unitary evolutions of the QW followed by a process of chirality-andposition measurement [13,14]. Let us take the origin as the initial position of the random walker with the initial condition |Ψ (0)⟩ of Eq.…”
Section: Periodic Measurements In the Chiralitymentioning
confidence: 99%
“…Here the obstacle of decoherence is present owing to imperfections and environmental noise. Several authors have studied the QW subjected to different types of coin operators and sources of decoherence to analyze and verify the principles of quantum theory as well as the passage from the quantum to the classical world [12][13][14][15][16][17]. These works have shown that the decoherence transforms the quantum behavior into a classical diffusive behavior.…”
Section: Introductionmentioning
confidence: 98%
“…A similar model is considered in Ref. [32], where the authors address the randomness induced by the frequent measurements. However, our case is differs fundamentally as we do not reset the coin state after every measurements and we focus on the entropic properties of the system.…”
Section: Discrete Time Quantum Walk As a Source Of Messagesmentioning
confidence: 99%
“…Discrete-time quantum walks (DTQWs) [16] offer a versatile platform for the exploration of a wide range of non-trivial geometric and topological phenomena (experiments) [9,17,18] and (theory) [10,[19][20][21][22][23][24][25][26][27][28][29][30]. Furthermore, QWs are robust platforms for modeling a variety of dynamical processes from excitation transfer in spin chains [31,32] to energy transport in biological complexes [33].…”
Section: Discrete-time Quantum Walksmentioning
confidence: 99%